Innate and adaptive immune evasion by dengue virus - Lee, Michelle Felicia; Voon, Guan Zhong; Lim, Hui Xuan; Chua, Mun Lok; Poh, Chit Laa (Frontiers in Cellular and Infection Microbiology, 2022)
Dengue is a mosquito-borne disease which causes significant public health concerns in tropical and subtropical countries. Dengue virus (DENV) has evolved various strategies to manipulate the innate immune responses of the host such as ‘hiding’ in the ultrastructure of the host, interfering with the signaling pathway through RNA modifications, inhibiting type 1 IFN production, as well as inhibiting STAT1 phosphorylation. DENV is also able to evade the adaptive immune responses of the host through antigenic variation, antigen-dependent enhancement (ADE), partial maturation of prM proteins, and inhibition of antigen presentation. miRNAs are important regulators of both innate and adaptive immunity and they have been shown to play important roles in DENV replication and pathogenesis. This makes them suitable candidates for the development of anti-dengue therapeutics. This review discusses the various strategies employed by DENV to evade innate and adaptive immunity. The role of miRNAs and DENV non-structural proteins (NS) are promising targets for the development of anti-dengue therapeutics.